THE FACTORS AFFECTING BENEFITS OF ENTERPRISE RESOURCE PLANNING SYSTEM FROM USER PERCEPTION (Third Sector Social Economic Review, 2019)
Enterprises make significant investments in technology and human resources, in order to add value to their operations in a highly competitive environment. One of the most important of these investments is the implementation of Enterprise Resource Planning (ERP) systems which require high cost and intensive time. ERP systems are computer based implementations with a modular structure that integrates all processes of the business from supply to customer service. System users, the sociological element of the system, are the main subject of this study. The main aim of this study is to determine the factors that increase the user acceptance value and benefits of system from the perspective of the users and the effects of these factors. For this purpose, the data obtained from the ERP system users (n=163)  of the businesses whose shares are traded in the Borsa Istanbul (BIST) 100 index were evaluated by Smart PLS 3.2.7 package program which allows analysis with Partial Least Squares - Structural Equation Model (PLS-SEM). As a result of the research, it has been determined that the system quality and service (provider) quality in the technological factors dimension, the shared common belief and system-work compliance in the organizational dimension, and the coordination in the environmental dimension are factors affecting the user value.
Keywords: Enterprise Resource Planning; User Value; Technology Organization Environment Model; Partial Least Squares Structural Equation Model.